Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Of course! Let's solve this problem step-by-step based on the information provided about the arithmetic progression (A.P.).
### Given:
1. The 11th term [tex]\(a_{11}\)[/tex] is -31.
2. The 21st term [tex]\(a_{21}\)[/tex] is -71.
We will determine:
a) The first term ([tex]\(a\)[/tex]),
b) The common difference ([tex]\(d\)[/tex]),
c) The 15th term ([tex]\(a_{15}\)[/tex]).
### Step-by-Step Solution
An arithmetic progression (A.P.) is characterized by the formula for the [tex]\(n\)[/tex]-th term:
[tex]\[ a_n = a + (n-1)d \][/tex]
where:
- [tex]\(a_n\)[/tex] is the [tex]\(n\)[/tex]-th term,
- [tex]\(a\)[/tex] is the first term,
- [tex]\(d\)[/tex] is the common difference,
- [tex]\(n\)[/tex] is the position of the term.
#### Step 1: Setting up the equations
Using the given terms:
1. For the 11th term:
[tex]\[ a_{11} = a + 10d = -31 \][/tex]
2. For the 21st term:
[tex]\[ a_{21} = a + 20d = -71 \][/tex]
#### Step 2: Solve for the common difference ([tex]\(d\)[/tex])
We have two equations:
[tex]\[ 1) \quad a + 10d = -31 \][/tex]
[tex]\[ 2) \quad a + 20d = -71 \][/tex]
Subtracting equation (1) from equation (2) to eliminate [tex]\(a\)[/tex]:
[tex]\[ (a + 20d) - (a + 10d) = -71 - (-31) \][/tex]
[tex]\[ 20d - 10d = -71 + 31 \][/tex]
[tex]\[ 10d = -40 \][/tex]
Solving for [tex]\(d\)[/tex]:
[tex]\[ d = \frac{-40}{10} \][/tex]
[tex]\[ d = -4.0 \][/tex]
So, the common difference [tex]\(d\)[/tex] is [tex]\(-4.0\)[/tex].
#### Step 3: Solve for the first term ([tex]\(a\)[/tex])
Substitute the value of [tex]\(d\)[/tex] back into equation (1):
[tex]\[ a + 10(-4.0) = -31 \][/tex]
[tex]\[ a - 40 = -31 \][/tex]
Solving for [tex]\(a\)[/tex]:
[tex]\[ a = -31 + 40 \][/tex]
[tex]\[ a = 9 \][/tex]
So, the first term [tex]\(a\)[/tex] is [tex]\(9\)[/tex].
#### Step 4: Find the 15th term ([tex]\(a_{15}\)[/tex])
Using the formula for the [tex]\(n\)[/tex]-th term:
[tex]\[ a_{15} = a + (15-1)d \][/tex]
[tex]\[ a_{15} = 9 + 14(-4.0) \][/tex]
[tex]\[ a_{15} = 9 - 56 \][/tex]
[tex]\[ a_{15} = -47.0 \][/tex]
So, the 15th term [tex]\(a_{15}\)[/tex] is [tex]\(-47.0\)[/tex].
### Summary of Results
a) The first term [tex]\(a\)[/tex] is [tex]\(9\)[/tex].
b) The common difference [tex]\(d\)[/tex] is [tex]\(-4.0\)[/tex].
c) The 15th term [tex]\(a_{15}\)[/tex] is [tex]\(-47.0\)[/tex].
### Given:
1. The 11th term [tex]\(a_{11}\)[/tex] is -31.
2. The 21st term [tex]\(a_{21}\)[/tex] is -71.
We will determine:
a) The first term ([tex]\(a\)[/tex]),
b) The common difference ([tex]\(d\)[/tex]),
c) The 15th term ([tex]\(a_{15}\)[/tex]).
### Step-by-Step Solution
An arithmetic progression (A.P.) is characterized by the formula for the [tex]\(n\)[/tex]-th term:
[tex]\[ a_n = a + (n-1)d \][/tex]
where:
- [tex]\(a_n\)[/tex] is the [tex]\(n\)[/tex]-th term,
- [tex]\(a\)[/tex] is the first term,
- [tex]\(d\)[/tex] is the common difference,
- [tex]\(n\)[/tex] is the position of the term.
#### Step 1: Setting up the equations
Using the given terms:
1. For the 11th term:
[tex]\[ a_{11} = a + 10d = -31 \][/tex]
2. For the 21st term:
[tex]\[ a_{21} = a + 20d = -71 \][/tex]
#### Step 2: Solve for the common difference ([tex]\(d\)[/tex])
We have two equations:
[tex]\[ 1) \quad a + 10d = -31 \][/tex]
[tex]\[ 2) \quad a + 20d = -71 \][/tex]
Subtracting equation (1) from equation (2) to eliminate [tex]\(a\)[/tex]:
[tex]\[ (a + 20d) - (a + 10d) = -71 - (-31) \][/tex]
[tex]\[ 20d - 10d = -71 + 31 \][/tex]
[tex]\[ 10d = -40 \][/tex]
Solving for [tex]\(d\)[/tex]:
[tex]\[ d = \frac{-40}{10} \][/tex]
[tex]\[ d = -4.0 \][/tex]
So, the common difference [tex]\(d\)[/tex] is [tex]\(-4.0\)[/tex].
#### Step 3: Solve for the first term ([tex]\(a\)[/tex])
Substitute the value of [tex]\(d\)[/tex] back into equation (1):
[tex]\[ a + 10(-4.0) = -31 \][/tex]
[tex]\[ a - 40 = -31 \][/tex]
Solving for [tex]\(a\)[/tex]:
[tex]\[ a = -31 + 40 \][/tex]
[tex]\[ a = 9 \][/tex]
So, the first term [tex]\(a\)[/tex] is [tex]\(9\)[/tex].
#### Step 4: Find the 15th term ([tex]\(a_{15}\)[/tex])
Using the formula for the [tex]\(n\)[/tex]-th term:
[tex]\[ a_{15} = a + (15-1)d \][/tex]
[tex]\[ a_{15} = 9 + 14(-4.0) \][/tex]
[tex]\[ a_{15} = 9 - 56 \][/tex]
[tex]\[ a_{15} = -47.0 \][/tex]
So, the 15th term [tex]\(a_{15}\)[/tex] is [tex]\(-47.0\)[/tex].
### Summary of Results
a) The first term [tex]\(a\)[/tex] is [tex]\(9\)[/tex].
b) The common difference [tex]\(d\)[/tex] is [tex]\(-4.0\)[/tex].
c) The 15th term [tex]\(a_{15}\)[/tex] is [tex]\(-47.0\)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.